1991
DOI: 10.1111/j.1365-2923.1991.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of computer-assisted instruction and small-group teaching of cardiac auscultation to medical students

Abstract: Cardiac auscultation is suffering from declining interest, caused by competing diagnostic technology and inadequate training of doctors. Computer-assisted instruction (CAI) supporting graphics and digitized sound could be ideally suited for teaching and sharpening this skill. To evaluate this premise we randomized 35 third-year medical students to 3 hours of seminar teaching plus the use of audiotapes (group 1), the self-use of a MacIntosh-based CAI (group 2), or both (group 3). All students took a pre- and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 9 publications
0
43
0
Order By: Relevance
“…There are many differences between the study of Mangione et al . (1991 ) and the present study, making comparisons difficult.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There are many differences between the study of Mangione et al . (1991 ) and the present study, making comparisons difficult.…”
Section: Discussionmentioning
confidence: 81%
“…Computer‐aided instruction of cardiac auscultation has previously been reported by Mangione et al . (1991 ), who compared pre‐ and post‐test results on 35 students divided into computer, seminar and combined groups.…”
Section: Discussionmentioning
confidence: 96%
“…Walsh and Bohn 13 demonstrated positive perception by medical students using a radiology program but no significant changes in test scores. Broader outcome measures were used by Mangione et al, 14 who demonstrated some qualitative differences but no differences in test scores in an auscultation tutorial used by an individual compared with small-group learning, and Garrett et al 15 used self-report scores of 23 thirdyear students to demonstrate perceived usefulness of a blood-smear teaching program.…”
Section: ⅲ Increase Attendancementioning
confidence: 99%
“…In the relatively sparse literature analysing teaching techniques of auscultation of the heart, a few factors for improving learning and performance have been noted. Principal among these is the importance of repetition of hearing the heart sounds, unsurprisingly as repetition is important in the acquisition of most skills.…”
mentioning
confidence: 99%